Pemetaan Literatur tentang Walisongo di Perpustakaan UIN Walisongo dan Pemanfaatannya oleh Pemustaka - Miswan, Miswan; Ulumi, Bahrul; Akyas, Gibran (Librarianship in Muslim Societies, 2023)
This study examines the development and mapping of printed literatures on “Walisongo”. The study aims to reveal the strength of the collection concerning Walisongo among other collections in the UIN Walisongo library. The results showed that the query "Walisongo" illustrates that the collection of walisongo stored in the library is only 0.091 % of the total number of existing collections. The mapping based on the conspectus shows that 14 titles (48.28 %) of the collection above are at the comprehensive level; 6 titles (20.69%) are included in the research level category; 3 titles (10.34 %) are included in the instructional support level; 3 titles (10.34 %) are categorized as basic information level; 2 titles (6.90%) are at minimum level; and only 1 title (3.45%) is in the out of scope category. The mapping based on subject analysis shows that the books about Walisongo mostly study the da'wah of Walisongo, which shows 34.48%. The rest examines the subject of tarekat, the history of Islam in Indonesia, biographies of Islamic figures, Sufism, mythology, fiqh, sects, and Javanese history. Furthermore, mapping based on loan data from circulation services shows that all books about Walisongo have been borrowed by users.